Management Analysis of the Provincial Municipality of Cusco2011 - 2014: Sector SG-5 Traditional Neighborhood of Santa Ana - Aragon Coricasa, Dayan (2021)
Between 2011 and 2014, the municipal management of the economist Luis Flores García, protagonist of the intervention of the Historic Center of Cusco, was developed. He outstanded for his social and cultural focus; However, actions to revalue the Cusco way, started controversy in the media; However, a large sector of the population remembers it with great affection because it supported the development of urban plans highly demanded. Some of his projects were almost imperceptible to the neighbors, but the technicians focused that these notably improved the quality of life of the citizens, in the medium and long term. This article analyzes this management and how it influenced the traditional neighborhood of Santa Ana.